The role of bathymetry, wave obliquity and coastal curvature in dune erosion prediction - Heijer, Cornelis den, 1979- (Deltares select series, 2013)
"Low lying coastal areas have always been attractive for people to live, but are also prone to flooding. In The Netherlands, half of the population lives in the coastal area below mean sea level where two-thirds of the economic value is located. Coastal dunes protect the hinterland from floodings as a primary sea defence along the major part of the Dutch coastline."--